Improving Hygienic Characteristics of Coated Electrodes for Welding High-Alloy Steels; IOP Conference Series: Earth and Environmental Science; Vol. 50 : Ecology and safety in the technosphere: current problems and solutions - Ilyashchenko D. P. Dmitry Pavlovich; Chinakhov D. A. Dmitriy Anatol'evich; Ivanov K. V.; Sadikov I. D. (2017, 2017)
Title screen